Nitrogen-doped coal-based graphene oxide and preparation method and application thereof

CN119898765BActive Publication Date: 2026-10-09CHINA ENERGY INVESTMENT CORP LTD +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202311404580.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-10-26
Publication Date
2026-10-09
Estimated Expiration
2043-10-26

AI Technical Summary

Technical Problem

[0011]当前,虽然已有一些用于CO2电催化制备乙醇的基于氮掺杂石墨烯的双金属催化剂的改进技术,但是,如何进一步提升这类催化剂在CO2电催化制备乙醇中的催化活性以及如何兼顾经济性等,依然属于本领域亟待取得突破的难题

Benefits of technology

[0054] 1. This invention is based on nitrogen-doped coal-based graphene oxide containing 5-12 wt% nitrogen and 30-45 wt% pyridine nitrogen. Using this support, a catalyst for the electroreduction of CO2 to ethanol can be prepared, and a catalyst with excellent catalytic activity can be obtained with relatively low active component dosage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119898765B_ABST
    Figure CN119898765B_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of electrocatalytic reduction of CO2 to prepare ethanol, and provides nitrogen-doped coal-based graphene as well as a preparation method and application thereof; the nitrogen-doped coal-based graphene based on the present application is conducive to obtaining a catalyst with better catalytic activity in the electrocatalytic reduction of CO2 to prepare ethanol. The preparation method comprises the following steps: S1, providing coal-based graphene; S2, nitrogen-doping the coal-based graphene to obtain nitrogen-doped coal-based graphene, wherein the nitrogen-doped coal-based graphene contains 5-12 wt% of nitrogen elements, and at least part of the nitrogen elements exist in the form of pyridine nitrogen, and the pyridine nitrogen accounts for 30-45 wt% of the total amount of the nitrogen elements.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of electrocatalytic reduction of CO2 to produce ethanol, specifically to a nitrogen-doped coal-based graphene oxide, its preparation method, and its application. Background Technology

[0002] Carbon dioxide capture, utilization, and storage (CCUS) is a necessary approach to reduce CO2 emissions from existing coal-fired power plants, coal chemical plants, and petrochemical plants. Since CO2 is a thermodynamically stable molecule, it is the result of the combustion of various carbon-containing chemical substances. Only under harsh reaction conditions such as high temperature, high pressure, and high overpotential can CO2 be converted into other carbon compounds. Electrochemical methods for reducing carbon dioxide offer environmental advantages such as mild reaction conditions (room temperature and pressure) and no secondary carbon emissions. This technology can convert CO2 into various high-value-added chemical raw materials and is a promising technology with large-scale application potential in CO2 utilization, leading to a continuous increase in research interest.

[0003] Depending on the catalyst used, CO2 electrocatalysis can produce a variety of different products, including C1 products (carbon monoxide, formic acid, methanol, methane) and C2+ products (ethylene, ethane, ethanol, propylene, n-propanol, etc.). Ethanol is an important chemical raw material. Furthermore, as a high-value product of deep CO2 reduction, ethanol is easy to separate, store, and transport, thus CO2 electrocatalysis for ethanol production has a wide range of applications.

[0004] In the electrocatalytic reduction of CO2, the first step is the activation of the CO2 molecule, which occurs when it reacts with one electron at a reduction potential of -1.9V relative to the standard hydrogen electrode to generate CO2. - Free radical intermediate. This step is relatively difficult because CO2 is a very stable linear molecule with low electron affinity; the breaking of C=O requires 750.0 kJ / mol. -1 The energy required for this process is limited, therefore this step is often considered the rate-determining step in the electrocatalytic CO2 reduction reaction. Furthermore, the hydrogen evolution reaction in the electrolyte competes fiercely with the adsorption and activation reaction of *CO; therefore, the most critical step for producing high-value-added ethanol is the conversion of CO2 to *CO.

[0005] The formation of multi-carbon (C2+) products requires complex multi-electron / proton coupling and C-C coupling, resulting in low Faraday efficiency for C2+ products. Among various metal CO2 RR electrocatalysts, copper is the only one with a negative adsorption energy for CO and a positive adsorption energy for H, thus enabling it to selectively reduce CO2 to various high-value-added C2+ products. However, copper catalysts often suffer from drawbacks such as broad product distribution, poor activity, low C2+ selectivity, and poor stability.

[0006] The bimetallic Cu-M tandem catalyst first reduces CO2 to CO on the M catalyst, followed by CC coupling on the Cu. Compared to directly reducing CO2 to CO without M and then performing CC coupling, the synergistic effect of the tandem mechanism increases the probability of CC coupling for ethanol production.

[0007] Each carbon atom in graphene is sp 2 The hybrid orbitals of graphene, combined with five carbon atoms to form a six-membered ring structure, possess excellent physicochemical properties, including large specific surface area, high electrical conductivity, tunable molecular structure, and resistance to acids and alkalis, making it widely used as a catalyst support material. In recent years, nitrogen-doped carbon materials have received considerable attention. Currently, various methods exist for preparing graphene with varying nitrogen contents, through in-situ or ex-situ synthesis. However, existing methods such as chemical vapor deposition and solvothermal methods suffer from high costs and complex processes, and the amount of nitrogen doping achieved in ex-situ is consistently very low, rarely exceeding 5%.

[0008] Patent application CN 115584525 A discloses a catalyst for the electrocatalytic synthesis of multi-carbon products from CO2 and its preparation method. The catalyst is CuInS with Cu-In dual active centers. 2-x Nanomaterials. The process includes the following steps: first, In₂S₃ with a flower-like, ruffled cluster structure is synthesized via a solvothermal reaction; then, Cu is doped into the defect sites of the flower-like, ruffled cluster In₂S₃ using an electrochemical ion substitution method, resulting in CuInS₃ with Cu-In dual active centers. 2-x Catalyst. This catalyst exhibits both high electrocatalytic activity for CO2 RR and high selectivity for C2+ products, which can significantly improve the energy efficiency of CO2 utilization.

[0009] Patent CN 115094442 A discloses a method for preparing a copper-nickel bimetallic nitrogen-carbon material and its application in the electrochemical reduction of carbon dioxide. The preparation method involves using C3N4 and graphene oxide as supports, and copper phthalocyanine and nickel phthalocyanine as the metal source and nitrogen source, respectively, with the nitrogen source introduced through ammoniation of the substrate. This preparation method is simple, economical, and easy to operate. The resulting catalytic material has a rich layered structure, with metal-based active sites uniformly distributed on both sides of the layered support. In the electrochemical reduction of CO2, it exhibits the characteristic of controllable adjustment of the CO and H2 ratio in the reduction products.

[0010] Patent CN 112264081 B discloses a bimetallic-nitrogen-doped monolithic carbon-based electrocatalyst for the electrochemical reduction of CO2 to ethanol and its preparation method. The method employs a competitive coordination crystallization method to prepare a precursor for the bimetallic-nitrogen-doped monolithic carbon-based electrocatalyst in a single step at room temperature and pressure. The precursor is then dried, pyrolyzed in an inert atmosphere, acid-washed, washed with water, and dried again to obtain the bimetallic-nitrogen-doped monolithic carbon-based electrocatalyst FexCu-NC. The carbon-based electrocatalyst prepared using bimetallic materials not only effectively reduces the catalyst preparation cost, but also significantly improves the catalytic performance due to the synergistic effect between the Fe and Cu bimetals. It can be directly used as a gas diffusion electrode for testing the electrochemical CO2 reduction reaction without the need for a binder, which is beneficial for the electrochemical reaction.

[0011] Currently, although there are some improved technologies for nitrogen-doped graphene-based bimetallic catalysts for the electrocatalytic production of ethanol from CO2, how to further enhance the catalytic activity of these catalysts in the electrocatalytic production of ethanol from CO2 and how to balance economic efficiency are still difficult problems that urgently need to be solved in this field. Summary of the Invention

[0012] This invention provides a nitrogen-doped coal-based graphene oxide, its preparation method, and its application. The nitrogen-doped coal-based graphene oxide based on this invention is beneficial for obtaining catalysts with better catalytic activity in the electrocatalytic reduction of CO2 to ethanol.

[0013] To achieve its objective, the present invention provides the following technical solution:

[0014] The first aspect of this invention provides a method for preparing nitrogen-doped coal-based graphene oxide, comprising the following steps:

[0015] S1 provides coal-based graphene oxide;

[0016] S2, nitrogen doping is performed on the coal-based graphene oxide to obtain nitrogen-doped coal-based graphene oxide, wherein the nitrogen-doped coal-based graphene oxide contains 5-12 wt% nitrogen element, and the nitrogen element exists at least partially in the form of pyridine nitrogen, the pyridine nitrogen accounting for 30-45 wt% of the total nitrogen element.

[0017] The inventors have discovered that nitrogen-doped coal-based graphene oxide, with a nitrogen content of 5-12 wt% and a doped nitrogen content of 30-45 wt% in the form of pyridine nitrogen, is beneficial as a support for obtaining electrocatalysts for the electrocatalytic reduction of CO2 to ethanol, particularly significantly improving the catalytic performance of Cu-Ag-based active metal element-based catalysts. The nitrogen-doped coal-based graphene oxide provided by this invention has specific nitrogen doping content and specific pyridine nitrogen doping amount. This support has strong electron affinity, serving as an adsorption site for CO2, effectively adsorbing and activating the reactant CO2. Simultaneously, the N atoms improve the conductivity of graphene, increase the positive charge density on adjacent carbon atoms, prevent protons from approaching, reduce hydrogen adsorption, and weaken the competition for the HER (hydrogen evolution reaction), exhibiting better ethanol yield and Faraday efficiency.

[0018] Preferably, in step S1, the thickness of the coal-based graphene oxide is 0.8-1.2 nm, and the sheet diameter is 500 nm-1 μm; more preferably, the purity of the coal-based graphene oxide is 98-100%, for example 98.4-99.5%. Nitrogen-doped coal-based graphene oxide obtained by nitrogen doping with the preferred coal-based graphene oxide has a thinner sheet-like morphology and is also beneficial for obtaining better conductivity. Subsequently, it can be used as a support to prepare an electrocatalytic reduction catalyst for CO2 to ethanol, which is beneficial for further improving catalytic performance.

[0019] Preferably, in step S1, the coal-based graphene oxide contains 0.1–0.7 wt% sulfur and 0.3–1 wt% potassium, for example, the potassium content is 0.32 wt%–1 wt%. The inventors have discovered that using coal-based graphene oxide containing small amounts of sulfur and potassium for subsequent nitrogen doping, and then using it as a support in a catalyst for the electrocatalytic reduction of CO2 to ethanol, can provide acidity and basicity to the catalyst, thereby improving its performance. The present invention relates to coal-based graphene oxide containing small amounts of S and K, which are derived from impurities in the coal. Preferably, the coal used in the present invention is sub-bituminous coal from the Shenfu Dongsheng mining area of ​​the Shendong Base in China, belonging to the Early Jurassic and / or Middle Jurassic periods. Its chemical composition mainly includes: C 66-67wt%, H 3.5-3.8wt%, S 0.4-0.5wt%, N 0.9-1.2wt%, O 12-15wt%, P 0.001-0.005wt%, and K 0.2-0.5wt%.

[0020] In some embodiments, in step S2, the nitrogen element exists in pyridine nitrogen, amino nitrogen, and pyrrole nitrogen, for example, the nitrogen doping forms are pyridine nitrogen, amino nitrogen, and pyrrole nitrogen. There is no particular limitation on the proportion of amino nitrogen and pyrrole nitrogen in the total nitrogen content, but the proportion of pyridine nitrogen must be 30-45 wt%.

[0021] In some preferred embodiments, in step S2, the nitrogen doping is performed using plasma etching. Preferably, the plasma etching method is dielectric barrier discharge plasma etching.

[0022] More preferably, the conditions for nitrogen doping via dielectric barrier discharge (DBD) plasma etching include: a power of 20–300 W, a nitrogen flow rate of 50–300 mL / min, a discharge time of 10–240 min, and an N2 purity of 99.0–100%; the nitrogen doping is preferably carried out at room temperature and pressure. The above nitrogen doping process is conducted in a DBD reactor, where coal-based graphene oxide reacts with a non-equilibrium nitrogen DC plasma arc, thereby incorporating N into the coal-based graphene oxide.

[0023] This invention employs plasma etching, particularly dielectric barrier discharge plasma etching, for nitrogen doping of coal-based graphene oxide. This method eliminates the need for high-temperature and high-pressure conditions, offering advantages such as high efficiency and environmental friendliness. Furthermore, the bonding form and nitrogen content of the doped nitrogen can be controlled by adjusting factors such as power and nitrogen flow rate during the doping process, thereby regulating and improving the graphene's performance. This allows for the easy acquisition of nitrogen-doped graphene with controllable target nitrogen content and doping positions. In contrast, existing techniques for preparing nitrogen-doped graphene often require high-temperature and high-pressure conditions and suffer from drawbacks such as uncontrollable nitrogen content and doping positions. This invention, through the aforementioned preferred method, can introduce a specific amount of nitrogen and a specific amount of pyridine nitrogen at specific positions into coal-based graphene oxide, significantly improving the performance of CO2 electrocatalytic ethanol production.

[0024] In some preferred embodiments, step S1 includes the following steps:

[0025] S1.1, Coal-based graphite is prepared using coal as a raw material;

[0026] S1.2, The coal-based graphene oxide is prepared by the Hummer method from the coal-based graphite.

[0027] In step S1.1, the preparation of coal-based graphite from coal can be carried out using conventional processes in the art. Specifically, the raw coal is subjected to high-temperature graphitization to obtain coal-based graphite; the coal can be crushed and screened before use, for example, high-temperature graphitization with 200-mesh coal powder; wherein the high-temperature graphitization temperature is, for example, 2500-3000℃, and the time is, for example, 1-5 hours, carried out in an inert gas atmosphere.

[0028] In step S1.2, the Hummer method is well known to those skilled in the art and can be performed with reference to existing Hummer process techniques. As a preferred embodiment, step S1.2 specifically includes the following steps:

[0029] S1.21, the coal-based graphite and sodium nitrate are stirred in concentrated sulfuric acid to obtain a mixed solution, and an oxidant is added to the mixed solution for intercalation oxidation treatment; the oxidant is preferably potassium permanganate, and the concentration of the concentrated sulfuric acid is preferably 95-100 wt%; the ratio of the amount of concentrated sulfuric acid to the amount of sodium nitrate is preferably (50-200):(1-3), in mL / g; the mass ratio of the amount of sodium nitrate to the amount of coal-based graphite is preferably (1-4):(0.5-2); the mass ratio of the amount of oxidant to the amount of coal-based graphite is preferably (3-10):(0.5-3);

[0030] S1.22, add a reducing agent to the reaction system to reduce the remaining oxidant; the reducing agent is preferably hydrogen peroxide, for example, 30wt% hydrogen peroxide; the amount of hydrogen peroxide used is sufficient to completely consume the residual oxidant in the reaction system; for example, in some embodiments, 2-6mL of 30wt% hydrogen peroxide is used relative to 5g of potassium permanganate.

[0031] S1.23, the obtained product is filtered, washed and dried to obtain the coal-based graphene oxide; the washing is preferably performed by first washing with dilute hydrochloric acid until the pH of the filtrate is 7-8, and then washing with a large amount of deionized water until the pH of the filtrate is 6-7, and the concentration of the dilute hydrochloric acid is preferably 1-3 mol / L.

[0032] More preferably, in step S1.21, after adding the oxidant, the temperature of the reaction system is controlled to not exceed 20°C and stirred for 30-60 minutes. Then, the temperature is raised to 20-50°C and stirring continues for 2-5 hours. Finally, the temperature is raised to 90-100°C for step S1.22. Specifically, after raising the temperature to 90-100°C, a portion of deionized water is slowly added and stirred, for example, for 15-30 minutes. The amount of deionized water used is, for example, 50-100 mL relative to 5g of oxidant. Then, the reducing agent is added, which can be added dropwise.

[0033] In some specific embodiments, in step S1.21, concentrated sulfuric acid and sodium nitrate can be mixed evenly to completely dissolve the sodium nitrate, for example, by stirring for 10-30 minutes, and then cooled in an ice-water bath, for example, by stirring for 5-10 minutes to cool the solution (the system temperature is not lower than 5°C). Then, coal-based graphite is added to the solution, and stirring is continued for 30-60 minutes to mix evenly to obtain a mixed solution.

[0034] In step S1.23, the drying can be oven drying, for example, drying at 80-100°C.

[0035] Through the above steps S1.1 and S1.2, coal-based graphene oxide with a thin sheet-like morphology can be obtained. Preferably, the thickness of the obtained coal-based graphene oxide is 0.8-1.2 nm, the sheet diameter is 500 nm-1 μm, and the purity is 98-100%.

[0036] Preferably, the coal used in step S1.1 is sub-bituminous coal from the Shenfu Dongsheng mining area of ​​the Shendong Base in China, belonging to the Early Jurassic and / or Middle Jurassic periods. Its chemical composition mainly includes C 66–67 wt%, H 3.5–3.8 wt%, S 0.4–0.5 wt%, N 0.9–1.2 wt%, O 12–15 wt%, P 0.001–0.005 wt%, and K 0.2–0.5 wt%. Using this preferred raw coal for the preparation of coal-based graphene oxide, specifically through steps S1.1 and S1.2, readily yields coal-based graphene oxide containing 0.1–0.7 wt% S and 0.3–1 wt% K. The nitrogen-doped coal-based graphene oxide prepared from this coal-based graphene oxide in subsequent steps, when used as a carrier in the electrocatalytic reduction of CO2 to ethanol, exhibits superior catalytic performance.

[0037] This invention uses inexpensive and abundant coal as a raw material to prepare graphene, which reduces the cost of catalysts and facilitates the large-scale production and application of nitrogen-doped coal-based graphene oxide.

[0038] A second aspect of the present invention also provides a nitrogen-doped coal-based graphene oxide containing 5-12 wt% nitrogen, wherein the nitrogen is present at least partially in the form of pyridine nitrogen, and the pyridine nitrogen is 30-45 wt% of the total nitrogen.

[0039] Preferably, the nitrogen-doped coal-based graphene oxide has a sheet-like morphology;

[0040] Preferably, the nitrogen element exists in the form of pyridine nitrogen, amino nitrogen, and pyrrole nitrogen;

[0041] Preferably, the nitrogen-doped coal-based graphene oxide is prepared using the preparation method described above. The details of the preparation method can be found in the preceding description and will not be repeated here.

[0042] A third aspect of the present invention also provides a nitrogen-doped graphene catalyst supported on an active metal element, wherein the catalyst is supported on nitrogen-doped coal-based graphene oxide prepared by the preparation method described above or on nitrogen-doped coal-based graphene oxide prepared by the preparation method described above.

[0043] The active metal elements loaded on the carrier include Cu and Ag; the molar ratio of Cu to Ag is preferably (3-6):1.

[0044] Using the nitrogen-doped coal-based graphene oxide of the present invention as a support, particularly as a support for a catalyst for the electrochemical reduction of CO2 to ethanol based on the active metal elements Cu and Ag, excellent catalytic performance can be obtained with relatively low amounts of active components. Preferably, based on the total mass of the catalyst, the total content of CuO and Ag2O (active components) does not exceed 6%, for example, 1-6%, and the content of CuO does not exceed 5%, for example, 1-5%.

[0045] When the above-mentioned catalyst is prepared using nitrogen-doped coal-based graphene oxide provided by this invention as a support, the support can effectively disperse the metal active components on its surface and expose a large number of active sites. The support contains 5-12 wt% nitrogen doping and 30-45 wt% pyridine nitrogen. The nitrogen-doped sites have strong electron affinity and can serve as adsorption sites and active sites for CO2, effectively adsorbing and activating the reactant CO2, which is beneficial for in-situ reduction of CO2 to generate the active intermediate *CO. Simultaneously, it can effectively anchor the metal active components, improving the dispersion of metal active components such as Cu, thereby increasing the activity per unit specific surface area. This allows for the achievement of good catalytic activity while significantly reducing the amount of metal active components (e.g., Cu and Ag), and simultaneously reducing costs. Using the nitrogen-doped coal-based graphene oxide provided by this invention as a support, the doped nitrogen atoms can improve the conductivity of graphene, increase the positive charge density on adjacent carbon atoms, prevent protons from approaching, reduce hydrogen adsorption, weaken the competition for HER, and exhibit better FE and ethanol yields. The catalyst obtained based on nitrogen-doped coal-based graphene oxide as a support in this invention exhibits significantly enhanced catalytic activity in the electrocatalytic production of ethanol from CO2.

[0046] The catalyst prepared by this invention exhibits improved activity in the electrocatalytic production of ethanol from CO2. For example, in some embodiments, at a potential of -1.2V vs. RHE, the ethanol Faradaic efficiency at room temperature and pressure is >90%, and the current density reaches, for example, 170–250 mA / cm². 2 .

[0047] A fourth aspect of the present invention also provides a method for preparing the nitrogen-doped graphene catalyst supported on an active metal element as described above, comprising the following steps:

[0048] The support is impregnated in an aqueous solution of a soluble salt of the active metal element, then the solvent is removed, and the catalyst is calcined under a protective atmosphere to obtain the catalyst.

[0049] Preferably, the calcination conditions include: calcination at a calcination temperature of 400–600°C, preferably for a calcination time of 3–8 hours; and preferably heating to the calcination temperature at a heating rate of 3–10°C / min.

[0050] In this invention, the inert gas or protective gas involved can be, for example, N2, Ar, He, etc.

[0051] Specifically, the soluble salt of the active metal element can be any type of soluble salt of the corresponding metal element that is conventional in the art, such as nitrates, sulfates, etc., and there are no particular limitations on this.

[0052] The fifth aspect of the present invention provides an application in which the catalyst described above or the catalyst prepared by the preparation method described above is used in the electrocatalytic reduction of CO2 to produce ethanol, or in which the nitrogen-doped coal-based graphene oxide prepared by the preparation method described above or the nitrogen-doped coal-based graphene oxide described above is used in the preparation of a catalyst for the electrocatalytic reduction of CO2 to produce ethanol.

[0053] The technical solution provided by this invention has the following beneficial effects:

[0054] 1. This invention is based on nitrogen-doped coal-based graphene oxide containing 5-12 wt% nitrogen and 30-45 wt% pyridine nitrogen. Using this support, a catalyst for the electroreduction of CO2 to ethanol can be prepared, and a catalyst with excellent catalytic activity can be obtained with relatively low active component dosage.

[0055] 2. This invention provides coal-based graphene from coal, a readily available and inexpensive raw material. The catalyst is also low-cost and easily scalable. The preparation method is simple; using the carrier of this invention to prepare a CO2 electroreduction catalyst for ethanol production reduces the amount of active component required, thus lowering costs.

[0056] 3. In a preferred embodiment, a suitable amount of nitrogen atoms can be controllably doped onto coal-based graphene at room temperature using plasma etching. The CO2 electroreduction catalyst prepared based on the obtained support can effectively stimulate the in-situ reduction of CO2 to generate the active intermediate *CO, reduce the reaction energy barrier, and improve the efficiency of CO2 electrocatalysis.

[0057] 4. Using the nitrogen-doped coal-based graphene oxide provided by this invention as a catalyst support can improve the dispersion of active components, increase the activity per unit specific surface area, thereby reducing the amount of active components used and reducing the cost of the catalyst.

[0058] 5. Compared with the prior art, the nitrogen-doped graphene CO2 electroreduction catalyst for ethanol production prepared by the present invention, which supports the active metal element Cu-Ag, can achieve a high ethanol yield and a high Faraday efficiency with a low active metal element content. Moreover, the entire preparation process has the characteristics of low cost and low energy consumption, and can be mass-produced.

[0059] 6. The nitrogen-doped graphene catalyst supported on active metal elements provided by this invention uses the nitrogen-doped coal-based graphene oxide of this invention as a support. This provides a large specific surface area, allowing for excellent dispersion of the active components, and also exhibits good conductivity, which is beneficial for improving the electrocatalytic effect. Using the nitrogen-doped coal-based graphene oxide of this invention as a support effectively anchors the active components, preventing agglomeration and thus increasing the activity per unit specific surface area of ​​the active components. This means that excellent catalytic effects can be achieved with a small amount of active components. The electrocatalytic reduction catalyst for ethanol from CO2 prepared based on the nitrogen-doped coal-based graphene oxide of this invention can promote C=C bond coupling and improve the yields of Fe and ethanol. Attached Figure Description

[0060] Figure 1 The diagram shows a schematic of the synthesis route of a bimetallic-supported N-doped graphene CO2 electrochemical reduction catalyst for ethanol production in one embodiment.

[0061] Figure 2 The image shown is a transmission electron microscope (TEM) image of coal-based graphene oxide from Example 1.

[0062] Figure 3 The figure shown is the N2 adsorption-desorption curve of coal-based graphene oxide in Example 1;

[0063] Figure 4 The image shown is the infrared spectrum of coal-based graphene oxide in Example 1;

[0064] Figure 5 The image shown is an XPS image of nitrogen-doped coal-based graphene oxide in Example 1;

[0065] Figure 6 The image shown is a scanning electron microscope (SEM) image of nitrogen-doped coal-based graphene oxide in Example 1.

[0066] Figure 7 The image shown is a scanning electron microscope (SEM) image of the bimetallic nitrogen-doped coal-based graphene oxide CO2 electrochemical reduction catalyst for ethanol production in Example 1.

[0067] Figure 8 The figure shows the ethanol Faraday efficiency measured at different electrode potentials in Example 1. Detailed Implementation

[0068] To facilitate understanding of the present invention, the following description, in conjunction with embodiments, will further illustrate the invention. It should be understood that the following embodiments are merely for a better understanding of the invention and do not imply that the invention is limited to these embodiments.

[0069] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains.

[0070] Where specific experimental steps or conditions are not specified in the examples, the corresponding conventional experimental steps or conditions in this technical field can be followed. Reagents or instruments whose manufacturers are not specified are all commercially available conventional products.

[0071] In the following embodiments, the catalyst prepared was tested for catalytic activity in the electrocatalytic reduction of CO2 to ethanol, and the reaction was carried out in a flow electrolyzer. The preparation of the working electrode and the assembly of the flow electrolyzer included:

[0072] (1) Preparation of the working electrode: 60 mg of catalyst material, 4 mL of isopropanol, and 240 μL of 5 wt% Nafion solution were mixed and then ultrasonically dispersed for 60 min to obtain a dispersion. The dispersion was then uniformly sprayed onto carbon paper with a microporous layer to obtain the working electrode. The catalyst loading on the working electrode was 1 mg / cm³. 2 ;

[0073] (2) A commercial flow electrolyzer system from GCL was used as the electrochemical CO2 reduction reaction device. The electrolyte solution was a KHCO3 aqueous solution with a concentration of 1 mol / L. The working electrode was the working electrode prepared in step (1) with an effective area of ​​2 × 2 cm. 2 The counter electrode is a platinum sheet electrode, and the reference electrode is a silver / silver chloride electrode.

[0074] (3) Assemble the three-electrode flow electrolytic cell system of step (2), use rubber pads to isolate each component, use a commercial anion exchange membrane (Foma, Germany) as the electrolyte diaphragm, and use clamps to fix the entire test system to ensure good airtightness.

[0075] The catalyst selectivity was tested using the potentiostatic method, and the catalytic products were detected by gas chromatography. The instrument was an Agilent GC7890B gas chromatograph with a thermal conductivity detector (TCD) and Ar as the carrier gas. The external standard method was used for quantification.

[0076] The potentials used in this invention are all measured using an Ag / AgCl electrode and converted to a reversible hydrogen electrode (RHE) using the following formula:

[0077] E(vs.RHE)=E(vs.Ag / AgCl)+0.21V+0.0591×pH

[0078] Where V is the voltage and pH is the pH value of the electrolyte (KHCO3 aqueous solution, 1 mol / L).

[0079] The Faraday efficiency (FE) is calculated as follows:

[0080]

[0081] Where FE is the Faraday efficiency in %; Z is the number of electrons transferred in the formation of ethanol, which is 12; n is the number of moles of ethanol, the target product, generated in the electrolysis process in mol; Qtotal is the total charge consumption in the electrolysis process in C; and F is the Faraday constant, 96485 C / mol.

[0082] In the following examples, the raw coal used is sub-bituminous coal from the Shenfu Dongsheng mining area of ​​the Shendong Base in China. It belongs to the Early Jurassic period and its chemical composition mainly includes C 66.14wt%, H 3.78wt%, S 0.41wt%, N 0.94wt%, O 12.45wt%, P 0.003wt%, K 0.3wt%, with the balance being volatile matter.

[0083] Example 1

[0084] The raw coal is crushed and screened to obtain 200-mesh coal powder, which is then set aside.

[0085] S1 provides coal-based graphene oxide.

[0086] S1.1, 100g of pulverized coal is graphitized at high temperature in a tubular furnace and calcined at 2800℃ in a N2 atmosphere for 2h to obtain coal-based graphite.

[0087] S1.2, The coal-based graphene oxide is prepared by the Hummer method from the coal-based graphite:

[0088] S1.21, 100 mL of concentrated sulfuric acid (98 wt%) and 2 g of sodium nitrate were added to a beaker one after another, and stirred for 30 min to dissolve all the sodium nitrate in the concentrated sulfuric acid. The beaker was then placed in an ice bath and stirred for 10 min to cool the solution (the system temperature should not be lower than 5 °C).

[0089] Add 1g of the prepared coal-based graphite to a beaker and continue stirring for 60 minutes to obtain a homogeneous mixture. Then, slowly add 5g of potassium permanganate to the mixture, controlling the reaction temperature to not exceed 20℃, and stir for 60 minutes. Next, heat the water bath to 35℃ and maintain this temperature for 4 hours with continuous stirring. Then, raise the temperature to 98℃, slowly add 100mL of deionized water, and magnetically stir for 30 minutes.

[0090] S1.22, then add 6 mL of 30 wt% hydrogen peroxide dropwise to the reaction system.

[0091] S1.23, the obtained reaction product is filtered, and then the filter residue is washed with 2 mol / L dilute hydrochloric acid until the pH of the filtrate is 7.5. Then it is washed with a large amount of deionized water until the pH of the filtrate is between 6 and 7. The washed product is then dried at 100℃ to obtain coal-based graphene oxide.

[0092] See the transmission electron microscope image of the prepared coal-based graphene oxide. Figure 2 ,from Figure 2 As can be seen, the coal-based graphene oxide exhibits a sheet-like morphology. The obtained coal-based graphene oxide has a thickness of 0.8 nm, a sheet diameter of 1 μm, and a specific surface area of ​​352.4 m². 2 / g, with a pore size of 6.5nm. The chemical composition of coal-based graphene oxide was determined by XRF analysis, showing a purity of 99.43%, containing trace amounts of S and K, with S content of 0.25wt% and K content of 0.32wt%. From... Figure 3 It can be seen that the prepared coal-based graphene oxide has typical mesoporous channels. From Figure 4 It can be seen that the prepared coal-based graphene oxide has no other impurity functional groups.

[0093] S2, Preparation of nitrogen-doped coal-based graphene oxide

[0094] Using the DBD plasma etching method, 1g of coal-based graphene oxide dried in step S1.23 was placed in a dielectric barrier discharge reactor. N2 was continuously introduced at a flow rate of 100mL / min with a purity of 99.9%. The dielectric barrier discharge reactor was turned on, and the discharge time was 50min. The dielectric barrier discharge (DBD) plasma power was 100W, resulting in nitrogen-doped coal-based graphene oxide material.

[0095] from Figure 5 The XPS plot shows that nitrogen was successfully incorporated into the coal-based graphene oxide, with a total nitrogen content of 10.8 wt%. Nitrogen exists in the forms of pyridine nitrogen, amino nitrogen, and pyrrole nitrogen, with pyridine nitrogen accounting for 44.3 wt%, amino nitrogen for 18.9 wt%, and pyrrole nitrogen for 36.8 wt%. Figure 6 It can be seen that the prepared nitrogen-doped coal-based graphene oxide has a sheet-like morphology.

[0096] S3, Preparation of Cu-Ag-supported nitrogen-doped graphene catalyst

[0097] An impregnation method was used to prepare a mixed solution by measuring 500 μL of 1 mol / L copper sulfate aqueous solution, 1000 μL of 0.125 mol / L silver nitrate aqueous solution, and 200 mL of deionized water. The mixed solution was added to 1 g of nitrogen-doped coal-based graphene oxide prepared in step S2, stirred, and evaporated to dryness by rotary evaporation at 120 °C. Then, it was calcined under N2 atmosphere with the following conditions: heating to 450 °C at a heating rate of 5 °C / min, and calcining at 450 °C for 5 h to obtain Cu-Ag supported nitrogen-doped graphene catalyst.

[0098] XRF analysis of the catalyst showed that, based on the total mass of the catalyst, the total content of active components (CuO and Ag2O) was 5.8 wt%, the CuO content was 4.6 wt%, and the molar ratio of Cu to Ag was 5.78:1.

[0099] from Figure 7 It can be seen that the Cu and Ag active components are uniformly distributed on the catalyst surface, with small particle size and no agglomeration.

[0100] The catalytic activity of the Cu-Ag-supported nitrogen-doped graphene catalyst prepared in Example 1 was tested in the electrocatalytic reduction of CO2 to ethanol. Figure 8 It can be seen that the Faraday efficiency of ethanol gradually increases with the increase of electrode potential, reaching 92% at -1.2V vs. RHE potential, with a current density of 236mA / cm². 2 .

[0101] Example 2

[0102] The raw coal is crushed and screened to obtain 200-mesh coal powder, which is then set aside.

[0103] S1 provides coal-based graphene oxide.

[0104] S1.1, 100g of pulverized coal is graphitized at high temperature in a tubular furnace and calcined at 2500℃ in a N2 atmosphere for 2h to obtain coal-based graphite.

[0105] S1.2, The coal-based graphene oxide is prepared by the Hummer method from the coal-based graphite:

[0106] S1.21, 100 mL of concentrated sulfuric acid (95 wt%) and 3 g of sodium nitrate were added to a beaker one after another, and stirred for 30 min to dissolve all the sodium nitrate in the concentrated sulfuric acid. The beaker was then placed in an ice bath and stirred for 20 min to cool the solution (the system temperature should not be lower than 5 °C).

[0107] Add 1g of the prepared coal-based graphite to a beaker and continue stirring for 80 minutes to obtain a homogeneous mixture. Then, slowly add 10g of potassium permanganate to the mixture, controlling the reaction temperature to not exceed 20℃, and stir for 60 minutes. Next, heat the water bath to 30℃ and maintain this temperature for 5 hours with continuous stirring. Then, raise the temperature to 100℃, slowly add 120mL of deionized water, and stir magnetically for 40 minutes.

[0108] S1.22, then add 8 mL of 30 wt% hydrogen peroxide dropwise to the reaction system.

[0109] S1.23, the obtained reaction product is filtered, and then the filter residue is washed with 2 mol / L dilute hydrochloric acid until the pH of the filtrate is 7.8. Then it is washed with a large amount of deionized water until the pH of the filtrate is between 6 and 7. The washed product is then dried at 100℃ to obtain coal-based graphene oxide.

[0110] The prepared coal-based graphene oxide was examined by transmission electron microscopy and showed to have a sheet-like morphology. The obtained coal-based graphene oxide had a thickness of 1.2 nm, a sheet diameter of 800 nm, and a specific surface area of ​​324.7 m². 2 / g, with a pore size of 7.2nm. The chemical composition of coal-based graphene oxide was determined by XRF analysis, and the purity was 99.45%, containing trace amounts of S and K, with S content of 0.1wt% and K content of 0.45wt%.

[0111] S2, Preparation of nitrogen-doped coal-based graphene oxide

[0112] Using the DBD plasma etching method, 1g of coal-based graphene oxide dried in step S1.23 was placed in a dielectric barrier discharge reactor. N2 was continuously introduced at a flow rate of 50mL / min with a purity of 99.9%. The dielectric barrier discharge reactor was turned on, and the discharge time was 10min. The dielectric barrier discharge (DBD) plasma power was 100W, thus obtaining nitrogen-doped coal-based graphene oxide material.

[0113] Testing revealed that the total nitrogen content in the nitrogen-doped coal-based graphene oxide material was 8.6 wt%, with nitrogen existing in the forms of pyridine nitrogen, amino nitrogen, and pyrrole nitrogen. Pyridine nitrogen accounted for 31.6 wt% of the total nitrogen content, amino nitrogen for 21.9 wt%, and pyrrole nitrogen for 46.5 wt%. The prepared nitrogen-doped coal-based graphene oxide exhibited a sheet-like morphology.

[0114] S3, Preparation of Cu-Ag-supported nitrogen-doped graphene catalyst

[0115] An impregnation method was used to prepare a mixed solution by measuring 500 μL of 1 mol / L copper sulfate aqueous solution, 800 μL of 0.125 mol / L silver nitrate aqueous solution, and 200 mL of deionized water. The mixed solution was added to 1 g of nitrogen-doped coal-based graphene oxide prepared in step S2, stirred, and evaporated to dryness by rotary evaporation at 120 °C. Then, it was calcined under N2 atmosphere with the following conditions: heating to 400 °C at a heating rate of 5 °C / min, and calcining at 400 °C for 6 h to obtain Cu-Ag supported nitrogen-doped graphene catalyst.

[0116] XRF analysis of the catalyst showed that, based on the total mass of the catalyst, the total content of active components (CuO and Ag2O) was 5.16 wt%, the CuO content was 4 wt%, and the molar ratio of Cu to Ag was 5:1.

[0117] The Cu-Ag-supported nitrogen-doped graphene catalyst prepared in Example 2 was tested for its catalytic activity in the electrocatalytic reduction of CO2 to ethanol. At -1.2 V vs. RHE potential, the ethanol Faraday efficiency was 90.5%, and the current density was 186 mA / cm². 2 .

[0118] Example 3

[0119] The raw coal is crushed and screened to obtain 200-mesh coal powder, which is then set aside.

[0120] S1 provides coal-based graphene oxide.

[0121] S1.1, 100g of pulverized coal is graphitized at high temperature in a tubular furnace and calcined at 3000℃ in an N2 atmosphere for 2 hours to obtain coal-based graphite.

[0122] S1.2, The coal-based graphene oxide is prepared by the Hummer method from the coal-based graphite:

[0123] S1.21, 100 mL of concentrated sulfuric acid (concentration of 98.3 wt%) and 1 g of sodium nitrate were added to a beaker one after another, and stirred for 30 min to dissolve all the sodium nitrate in the concentrated sulfuric acid. The beaker was then placed in an ice bath and stirred for 10 min to cool the solution (the system temperature should not be lower than 5 °C).

[0124] Add 1g of the prepared coal-based graphite to a beaker and continue stirring for 60 minutes to obtain a homogeneous mixture. Then, slowly add 3g of potassium permanganate to the mixture, controlling the reaction temperature to not exceed 20℃, and stir for 60 minutes. Next, heat the water bath to 50℃ and maintain this temperature for 4 hours with continuous stirring. Then, raise the temperature to 100℃, slowly add 80mL of deionized water, and magnetically stir for 30 minutes.

[0125] S1.22, then add 5 mL of 30 wt% hydrogen peroxide dropwise to the reaction system.

[0126] S1.23, the obtained reaction product is filtered, and then the filter residue is washed with 2 mol / L dilute hydrochloric acid until the pH of the filtrate is 8. Then it is washed with a large amount of deionized water until the pH of the filtrate is between 6 and 7. Then the washed product is dried at 100℃ to obtain coal-based graphene oxide.

[0127] The prepared coal-based graphene oxide was examined by transmission electron microscopy and showed to have a sheet-like morphology. The obtained coal-based graphene oxide had a thickness of 1.1 nm, a sheet diameter of 520 nm, and a specific surface area of ​​328.7 m². 2 / g, with a pore size of 6.9nm. The chemical composition of coal-based graphene oxide was determined by XRF analysis, and the purity was 98.4%, containing trace amounts of S and K, with S content of 0.68wt% and K content of 0.92wt%.

[0128] S2, Preparation of nitrogen-doped coal-based graphene oxide

[0129] Using the DBD plasma etching method, 1g of coal-based graphene oxide dried in step S1.23 was placed in a dielectric barrier discharge reactor. N2 was continuously introduced at a flow rate of 300mL / min with a purity of 99.9%. The dielectric barrier discharge reactor was turned on, and the discharge time was 240min. The dielectric barrier discharge (DBD) plasma power was 100W, thus obtaining nitrogen-doped coal-based graphene oxide material.

[0130] Testing revealed that the total nitrogen content in the nitrogen-doped coal-based graphene oxide material was 12 wt%, with nitrogen existing in the forms of pyridine nitrogen, amino nitrogen, and pyrrole nitrogen. Pyridine nitrogen accounted for 42 wt% of the total nitrogen content, amino nitrogen for 22.1 wt%, and pyrrole nitrogen for 35.9 wt%. The prepared nitrogen-doped coal-based graphene oxide exhibited a sheet-like morphology.

[0131] S3, Preparation of Cu-Ag-supported nitrogen-doped graphene catalyst

[0132] An impregnation method was used to prepare a mixed solution by measuring 500 μL of 1 mol / L copper sulfate aqueous solution, 900 μL of 0.125 mol / L silver nitrate aqueous solution, and 300 mL of deionized water. The mixed solution was added to 1 g of nitrogen-doped coal-based graphene oxide prepared in step S2, stirred, and evaporated to dryness by rotary evaporation at 120 °C. Then, it was calcined under N2 atmosphere with the following conditions: heating to 600 °C at a heating rate of 5 °C / min, and calcining at 600 °C for 3 h to obtain Cu-Ag supported nitrogen-doped graphene catalyst.

[0133] XRF analysis of the catalyst showed that, based on the total mass of the catalyst, the total content of active components (CuO and Ag2O) was 5.3 wt%, the CuO content was 4 wt%, and the molar ratio of Cu to Ag was 4.5:1.

[0134] The Cu-Ag-supported nitrogen-doped graphene catalyst prepared in Example 3 was tested for its catalytic activity in the electrocatalytic reduction of CO2 to ethanol. At -1.2 V vs. RHE potential, the ethanol Faraday efficiency was 91.6%, and the current density was 203 mA / cm². 2 .

[0135] Comparative Example 1

[0136] The procedure was carried out in accordance with Example 1, except that in step S2, when preparing nitrogen-doped coal-based graphene oxide, the N2 flow rate was 100 mL / min, the N2 purity was 99.9%, the dielectric barrier discharge reactor was turned on, the discharge time was 2 min, and the dielectric barrier discharge (DBD) plasma power was 100 W. All other procedures were carried out in accordance with Example 1.

[0137] Testing revealed that the total nitrogen content in the prepared nitrogen-doped coal-based graphene oxide was 2.3 wt%, with pyridine nitrogen accounting for 13.7 wt% of the total nitrogen content.

[0138] Experimental Results: The catalyst prepared in Comparative Example 1 was tested for catalytic activity according to Example 1. At a potential of -1.2 V vs. RHE, the ethanol Faraday efficiency was 85.3%, and the current density was 178.3 mA / cm². 2 .

[0139] Comparative Example 2

[0140] The experiment was conducted in accordance with Example 1, except that step S2 was omitted, i.e., nitrogen doping was not performed. Instead, the coal-based graphene oxide prepared in step S1 was used as a carrier to perform copper and silver loading experiments in step S3 of Example 1.

[0141] Experimental Results: The catalyst prepared in Comparative Example 2 was tested for catalytic activity according to Example 1. At a potential of -1.2 V vs. RHE, the ethanol Faraday efficiency was 63.4%, and the current density was 128.9 mA / cm². 2 .

[0142] Comparative Example 3

[0143] The catalyst was prepared by co-precipitation without a support.

[0144] The catalyst consists of oxides of copper and silver. The molar ratio of copper to silver is the same as in Example 1.

[0145] Prepare a mixed solution by measuring 50 mL of 1 mol / L copper sulfate aqueous solution, 100 mL of 0.125 mol / L silver nitrate aqueous solution, and 200 mL of deionized water. Heat the mixed solution to 55 °C, add 150 mL of 1 mol / L NaOH aqueous solution dropwise, and react for 0.5 h. Add 5 g of ascorbic acid, react for 5 h, centrifuge, wash 5 times with deionized water, and dry at 80 °C to obtain Cu. x Ag y O2 catalyst.

[0146] Experimental Results: The catalyst prepared in Comparative Example 3 was tested for catalytic activity according to Example 1. At a potential of -1.2 V vs. RHE, the ethanol Faraday efficiency was 33.9%, and the current density was 67.5 mA / cm². 2 .

[0147] Comparative Example 4

[0148] The procedure was carried out in accordance with Example 1, except that in step S3, silver nitrate was replaced with barium nitrate. In this comparative example, the molar ratio of Cu to Ba in the catalyst was the same as that of Cu to Ag in the catalyst of Example 1.

[0149] Experimental Results: The catalyst prepared in Comparative Example 4 was tested for catalytic activity according to Example 1. At a potential of -1.2 V vs. RHE, the ethanol Faradaic efficiency was 55.6%, and the current density was 78.8 mA / cm². 2 .

[0150] Comparative Example 5

[0151] The process was carried out in accordance with Example 1, except that silver nitrate was not used in step S3, and the only active metal element in the resulting catalyst was Cu. The CuO content in the catalyst obtained in this comparative example was the same as that in Example 1.

[0152] Experimental Results: The catalyst prepared in Comparative Example 5 was tested for catalytic activity according to Example 1. At a potential of -1.2 V vs. RHE, the ethanol Faraday efficiency was 2.7%, and the current density was 24.8 mA / cm².2 .

[0153] Table 1. Catalyst activity test results at -1.2V vs. RHE potential

[0154]

[0155] It is readily understood that the above embodiments are merely illustrative examples for clear explanation and do not imply that the invention is limited thereto. Those skilled in the art will recognize that other variations or modifications can be made based on the above description. It is neither necessary nor possible to exhaustively list all possible implementations. However, obvious variations or modifications derived therefrom remain within the scope of protection of this invention.

Claims

1. A nitrogen-doped graphene catalyst supported on an active metal element for the electrocatalytic reduction of CO2 to ethanol, characterized in that, The catalyst uses nitrogen-doped coal-based graphene oxide as a support, and the active metal elements loaded on the support include Cu and Ag. Based on the total mass of the catalyst, the total content of CuO and Ag2O is 1~6%, and the content of CuO is 1~4.6%. The molar ratio of Cu to Ag is (3~6):

1. The method for preparing nitrogen-doped coal-based graphene oxide is characterized by comprising the following steps: S1 provides coal-based graphene oxide; S2, nitrogen doping is performed on the coal-based graphene oxide to obtain nitrogen-doped coal-based graphene oxide, wherein the nitrogen-doped coal-based graphene oxide contains 5-12 wt% nitrogen element, and the nitrogen element exists at least partially in the form of pyridine nitrogen, wherein the pyridine nitrogen accounts for 30-45 wt% of the total nitrogen element; In step S2, the nitrogen doping is performed using plasma etching, specifically dielectric barrier discharge plasma etching. The conditions for nitrogen doping using dielectric barrier discharge plasma etching include: a power of 20-300W, a nitrogen flow rate of 50-300mL / min, a discharge time of 10-240min, and an N2 purity of 99.0-100%. The nitrogen doping is performed at room temperature and pressure.

2. The catalyst according to claim 1, characterized in that, In step S1, the thickness of the coal-based graphene oxide is 0.8-1.2 nm, and the sheet diameter is 500 nm-1 µm; the purity of the coal-based graphene oxide is 98-100%.

3. The catalyst according to claim 2, characterized in that, The purity of the coal-based graphene oxide is 98.4-99.5%.

4. The catalyst according to any one of claims 1-3, characterized in that, In step S1, the coal-based graphene oxide contains 0.1-0.7 wt% S and 0.3-1 wt% K.

5. The catalyst according to claim 4, characterized in that, In step S1, the K content in the coal-based graphene oxide is 0.32wt%-1wt%.

6. The catalyst according to any one of claims 1-3, characterized in that, In step S2, the nitrogen element exists in the form of pyridine nitrogen, amino nitrogen, and pyrrole nitrogen.

7. The catalyst according to any one of claims 1-3, characterized in that, Step S1 includes the following steps: S1.1, coal-based graphite is prepared using coal as raw material; the coal is subjected to high-temperature graphitization at 2500-3000℃ to prepare the coal-based graphite; S1.2, The coal-based graphene oxide is prepared by the Hummer method from the coal-based graphite; Step S1.2 specifically includes the following steps: S1.21, the coal-based graphite and sodium nitrate are stirred in concentrated sulfuric acid to obtain a mixed solution, and an oxidant is added to the mixed solution for intercalation oxidation treatment; the oxidant is potassium permanganate, and the concentration of the concentrated sulfuric acid is 95-100 wt%; the ratio of the amount of concentrated sulfuric acid to sodium nitrate is (50~200):(1~3), in mL / g; the mass ratio of sodium nitrate to coal-based graphite is (1~4):(0.5~2); the mass ratio of the oxidant to coal-based graphite is (3~10):(0.5~3); S1.22, Add a reducing agent to the reaction system to reduce the remaining oxidizing agent; S1.23, the obtained product is filtered, washed and dried to obtain the coal-based graphene oxide.

8. The catalyst according to claim 7, characterized in that, In step S1.1, the coal is sub-bituminous coal from the Shenfu Dongsheng mining area, belonging to the Early Jurassic and / or Middle Jurassic periods. Its chemical composition mainly includes C 66~67wt%, H 3.5~3.8wt%, S 0.4~0.5wt%, N 0.9~1.2wt%, O 12~15wt%, P 0.001~0.005wt%, and K 0.2~0.5wt%.

9. The catalyst according to claim 7, characterized in that, In step S1.22, the reducing agent is hydrogen peroxide.

10. The catalyst according to claim 7, characterized in that, In step S1.23, the washing process involves first washing with dilute hydrochloric acid until the pH of the filtrate is 7-8, and then washing with deionized water until the pH of the filtrate is 6-7. The concentration of the dilute hydrochloric acid is 1-3 mol / L.

11. The catalyst according to claim 7, characterized in that, In step S1.21, after adding the oxidant, the temperature of the reaction system is controlled to not exceed 20°C and stirred for 30-60 minutes. Then, the temperature is raised to 20-50°C and stirring is continued for 2-5 hours. Finally, the temperature is raised to 90-100°C to proceed with step S1.

22.

12. A method for preparing the catalyst according to any one of claims 1-11, characterized in that, Includes the following steps: The support is impregnated in an aqueous solution of a soluble salt of the active metal element, then the solvent is removed, and the catalyst is calcined under a protective atmosphere to obtain the catalyst. The calcination conditions include calcination at a temperature of 400~600℃.

13. The preparation method according to claim 12, characterized in that, The calcination time is 3 to 8 hours.

14. The preparation method according to claim 12, characterized in that, The temperature is increased to the calcination temperature at a heating rate of 3~10℃ / min.

15. An application characterized in that, The catalyst according to any one of claims 1-11 or the catalyst prepared by any one of claims 12-14 is used in the electrocatalytic reduction of CO2 to produce ethanol.

Citation Information

Patent Citations

  • A bimetallic-nitrogen-doped monolithic carbon-based electrocatalyst for the electrochemical reduction of CO2 to ethanol and its preparation method.

    CN112264081B

  • Catalyst for synthesizing multi-carbon product through electrocatalysis of CO2 and preparation method of catalyst

    CN115584525A

  • Nitrogen-doped graphene oxide material and preparation method thereof

    CN103803539A

  • Method for preparing cold plasma N-doped porous graphene

    CN106219533A

  • Preparation method and application of lamellar Cu-based N-doped graphene catalyst

    CN114836781A